Internacionalização em PME: análise da cadeia de piscicultura no processo de exportação de pescado no município de Rio Preto da Eva - Santos, Euler Erlanger Ribeiro dos (Brasil, 2023)
The internationalization of a Small and Medium Enterprise (SME) is linked to the process of expanding its activities to the external environment, aiming at participating in new markets, increasing the number of sales, improving product quality, growing the company's portfolio, developing of new marketing strategies and partnership opportunities. However, these dimensions, when applied to SMEs in Brazil, remain a complex process, from the design of the production chain to the selection of consumer markets. In the state of Amazonas, fish farming has strategic peculiarities capable of reaching foreign markets due to various conditions such as climate, water and biological diversity among native fish species. Understanding not only the productive organisms, but the link between man and his interaction with biodiversity involves the adoption of a case study strategy in unveiling the internationalization phenomenon. Aiming to study in a more dense way the intrinsic interests of the interlocutors of these organizations, and the relationship with internationalization, the case study strategy, intermediated by the triangulation of collection/analysis methods, provides the understanding about the organizational modes and the desired search for export expansion of fish farming aiming at new markets. This perspective advocates the understanding of local management, and the parallelism of organizational patterns of the market, not only internal, but also external. The aim is, therefore, to understand the potential for Internationalization of SMEs in the fish farming chain in the municipality of Rio Preto da Eva.